Integrating micro-hydro and solar PV in rainwater harvesting: A hybrid generation approach - Mohd Nasir, Mohamad Na'im; Mohd Salleh, Muhammad Zafran; Bohari, Zul Hasrizal; Sulaima, Mohamad Fani; Ahmad, Emy Zairah; Baharom, Mohamad Faizal; Ping, Jack Soh (Penerbit Akademia Baru, 2024)
As the scarcity of water worsens and the frequency of severe weather increases, the efficient harvesting of rainwater becomes more critical. Despite its potential to conserve water and mitigate flooding, the integration of rainwater harvesting with solar PV and micro-hydro technologies remains underutilized in renewable energy production. A significant barrier to widespread adoption is the challenge of accurately quantifying energy generation and optimizing management practices. This project aims to address these issues by proposing a method to develop a rainwater harvesting system that integrates solar PV and micro-hydro technologies. The primary objective is to evaluate the practical performance of this hybrid system in driving applications such as irrigation and sanitation. The findings demonstrate that the integrated system outperforms conventional methods, suggesting its effectiveness in rainwater utilization as a renewable energy resource.